Synoptic and Climatic Conditions of an Extreme Snowstorm Event Over Northeast China and Its Climate Predictability - Wang, Lushan; Fan, Ke (Frontiers in Earth Science, 2022)
A blizzard struck Northeast China in November 2020, and the maximum daily snowfall broke its record since 1961. The synoptic and climatic conditions and the predictability of this extreme snowstorm event are examined by using the daily National Centers for Environmental Prediction (NCEP) reanalysis and the second version of the NCEP Climate Forecast System (CFSv2). The results show that an anomalous anticyclone over Japan and an anomalous cyclone in South China supplied abundant moisture and the rapidly enhanced Siberian high triggered the snowstorm. Before the snowstorm, the positive North Pacific Oscillation (NPO) and North Atlantic Oscillation (NAO) were essential for the accumulated water vapor. In addition, we find that the monthly NPO index and NAO index in November 2020 are both extremely strong compared to 1979–2019, and their combination converges to create the extreme snowstorm-related atmospheric circulation. The positive NPO and NAO together induce an anomalous anticyclone in Japan, which provides southerly water vapor transport to Northeast China. The midlatitude North Pacific warm sea surface temperature (SST) contributes to the positive NPO, and the Atlantic SST anomalies impact the positive NAO. However, the La Niña condition in 2020 might not be a key factor influencing the snowstorm. Finally, the subseasonal–seasonal skillful prediction of the snowfall can be made up to 3 days in advance. The CFSv2 had limited skill in forecasting the snowfall, NAO and NPO in November 2020. Improved predictability of extreme snowfall events is still needed.